Evaluation of the antioxidant activity of coral mucus isolated from Porites lobata in vitro - Nguyen , Thi Phuong Thao; Ta, Thi Thu Thuy; Bui, Van Ngoc (Vietnam Journal of Biotechnology, 2025)
Marine-derived natural products have attracted much interest from scientists (chemists and pharmacologists), since many of their potential bioactivities are still unexplored. Among marine natural products discovered to date, 56% are anticancer, 13% are antibacterial, 5% are antifungal, and 3% are antiviral compounds. These compounds come from green algae (1%), red algae (4%), brown algae (5%), sponges (31%), corals (24%), and marine microorganisms (15%). Coral reefs, especially Porites lobata, secrete surface mucus layers (SMLs) that serve as essential barriers in host defense and microbial regulation. However, environmental stressors such as bleaching may alter the biochemical composition of this mucus, compromising its biological functions. This study aimed to compare the antioxidant properties of mucus obtained from healthy and bleached P. lobata corals to assess the impact of bleaching on their natural protective capabilities. The DPPH assay and flow cytometry with dihydroethidium (DHE) staining were used to evaluate the free radical scavenging activity and antioxidant capacity of coral surface mucus layer samples. The antioxidant activity of healthy coral mucus was significantly higher than that of bleached mucus, with a 2-fold increase at 1/5 and 1/10 dilutions, and nearly a 2.8-fold increase at 1/20 dilution. The results indicate that mucus from healthy corals exhibited significantly higher antioxidant activity than that from bleached corals. DPPH analysis showed stronger radical scavenging ability in healthy mucus extracts, while flow cytometry demonstrated a marked reduction in reactive oxygen species (ROS) accumulation in treated HCT116 cells compared to both bleached mucus and control groups. These findings suggest a decline in the coral’s natural defense mechanisms post-bleaching. The mucus from healthy corals has the ability to reduce the accumulation of intracellular ROS in HCT116 cells, indicating its potential to against oxidative stress-related diseases. The robust antioxidant activity of healthy coral mucus highlights its potential as a source of novel marine-derived antioxidants. This study supports further investigation into the bioactive compounds from the surface mucus layer of healthy Porites spp. corals for potential therapeutic applications against oxidative stress-related diseases.